Correlation Physical Activity, Energy Balance, and Metabolic Syndrome of Physical Fitness in Elderly Age Group (Majalah Kedokteran Bandung, 2018)
Fitness becomes an important benchmark for public health in every age group. Activities with poor adverse fitness are at risk of injury. Good fitness is gained from a balance in everyday physical activity with conditions that are free of metabolic syndrome. This study investigated the relationship of physical activity, energy balance, and metabolic syndrome to the fitness of 166 professors of Universitas Padjadjaran who underwent a 1-month fitness checkup at BAPELKES Bandung in the period of 2017. Based on the regression analysis, the results showed a significant relationship between physical activity, energy balance, and metabolic syndrome on the physical fitness of the elderly group (F = 25.9290> F table = 2.427) with normal data distribution (Kolmogorov-Smirnov test). The results also showed a moderate relationship (R = 0.569 and R2 = 0.324). It also partially showed significant influence between physical activity and fitness (t = 8.541> t table = 1.975), significant influence between energy balance and physical fitness (t = 2.248> t table = 1.975), and no significant partial influence between metabolic syndrome and physical fitness of the elderly group (t = -0.029 Ftable=2,427) dengan distribusi data normal (tes Kolmogorov-Smirnov). Hasil juga menunjukkan hubungan yang moderat (R= 0,569 dan R2= 0,324). Secara parsial juga menunjukkan pengaruh yang signfikan aktivitas fisik dengan kebugaran (t= 8.541> t tabel= 1.975), pengaruh signifikan keseimbangan energi dengan kebugaran fisik (t= 2,248> t tabel= 1,975), dan tidak ada pengaruh signifikan secara parsial terhadap sindrom metabolik dengan kebugaran fisik kelompok usia lanjut (t= -0,029 < t tabel= 1,975). Berdasar atas hasil penelitian dapat disimpulkan hubungan = aktivitas fisik, keseimbangan energi, dan sindrom metabolik dengan kebugaran fisik guru besar Universitas Padjadjaran.Kata kunci: Kebugaran, keseimbangan energi, sindrom metabolik
Keywords: Energy balance; metabolic syndrome; physical fitness